Mn-doped nanocrystals in light-emitting diodes: energy-transfer to obtain electroluminescence from quantum dots - Rath, Arup Kumar; Bhaumik, Saikat; Pal, Amlan J. (Applied Physics Letters, 2010)
We fabricatelight-emitting diodes(LEDs) based on Mn-doped ZnSnanocrystals along with hole-transporting bis(3-methylphenyl)--diphenyl-benzidine (TPD). With Mn-doping, ZnSnanostructures exhibit a strong photoluminescence. The LEDs exhibit electroluminescence(EL) from Mn-doped ZnSquantum dots and TPD. In order to open up channels for energy-transfer from TPD to quantum dots and to achieve EL from only the nanoparticles, we grow core-shell nanoparticles with Mn-doped ZnS in the core and CdS as the shell layer. Excitons formed in TPD can now transfer their energy directly to the shell-layer to yield EL from only the nanoparticles.

Magnetic chemiresistive Fe-doped In2O3 nanocubes to Tunably detect NO2 at ppm to ppb concentrations - Rudra, Pratyasha; Dambhare, Neha V.; Srihari, Velaga; Das, Sagnik; Rath, Arup Kumar; Saha, Debdulal; Mondal, Swastik (ACS APPLIED NANO MATERIALS, 2024)
Keywords: GAS-SENSING PROPERTIES; METAL-OXIDE NANOSTRUCTURES